Feminism in Pramoedya Ananta Toer’s Novel Gadis Pantai - Febrina, D (KnE Social Sciences, 2018)
This study deals with the life of woman in the novel Gadis Pantai by Pramoedya Ananta Toer. The purposes of this study are to analyze and described feminism in Pramoedya Ananta Toer’s novel using theory of feminism proposed by Clark (1990). Feminism is then a belief that women should be equal to men and now are not, and that it is also any actions, especially organized, that promote women’s rights to move towards equality with men. Feminism addresses economic, social, political and cultural disparities of power and rights. The study focused on rights of living allowance and nursing children. Qualitative method is applied in this study supported by Bogdan and Biklen (1992: 59). The source of data in this study consists of two types, i.e. primary data and secondary data. The primary data is the novel by Pramoedya Ananta Toer and the secondary data are documents, script and other relevant sources. The data are collected by using content analysis. The result of this study shows that feminism theory on living allowance and nursing children are clearly reflected in the novel by the character of Gadis Pantai. Keywords: feminism, living allowance, nursing children